PENGEMBANGAN MEDIA VIDEO TUTORIAL PEMBUATAN POLA CELANA DI FASE E SMK NEGERI 2 JOMBANG - Risma Ayu Tri Utami; Mita Yuniati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The learning process of trouser pattern making in the Basic Fashion subject for Phase E students at SMK Negeri 2 Jombang still faces several challenges, particularly the limited time available for practical learning and the low ability of students to recall the pattern-making procedures, which affects their practical skills. These conditions highlight the need for the development of learning media that can be accessed independently and repeatedly, one of which is a video tutorial. This study aimed to develop a video tutorial for trouser pattern making, determine its feasibility based on evaluations by material, media, and language experts, and examine students' skill outcomes after using the media. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The research subjects were tenth-grade students of the Fashion Design and Production program at SMK Negeri 2 Jombang. Data were collected through expert validation questionnaires and students' practical skill assessment sheets and were analyzed using descriptive quantitative techniques. The results showed that the developed video tutorial achieved a